The investigation of minoxidil-induced [Ca2+]i rises and non-Ca2+-triggered cell death in PC3 human prostate cancer cells. (2nd January 2017) - Chen, I-Shu; Chou, Chiang-Ting; Liu, Yuan-Yuarn; Yu, Chia-Cheng; Liang, Wei-Zhe; Kuo, Chun-Chi; Shieh, Pochuen; Kuo, Daih-Huang; Chen, Fu-An; Jan, Chung-Ren
Abstract: Minoxidil is clinically used to prevent hair loss. However, its effect on Ca 2+ homeostasis in prostate cancer cells is unclear. This study explored the effect of minoxidil on cytosolic-free Ca 2+ levels ([Ca 2+ ]i ) and cell viability in PC3 human prostate cancer cells. Minoxidil at concentrations between 200 and 800 μM evoked [Ca 2+ ]i rises in a concentration-dependent manner. This Ca 2+ signal was inhibited by 60% by removal of extracellular Ca 2+ . Minoxidil-induced Ca 2+ influx was confirmed by Mn 2+ -induced quench of fura-2 fluorescence. Pre-treatment with the protein kinase C (PKC) inhibitor GF109203X, PKC activator phorbol 12-myristate 13 acetate (PMA), nifedipine and SKF96365 inhibited minoxidil-induced Ca 2+ signal in Ca 2+ containing medium by 60%. Treatment with the endoplasmic reticulum Ca 2+ pump inhibitor 2, 5-ditert-butylhydroquinone (BHQ) in Ca 2+ -free medium abolished minoxidil-induced [Ca 2+ ]i rises. Conversely, treatment with minoxidil abolished BHQ-induced [Ca 2+ ]i rises. Inhibition of phospholipase C (PLC) with U73122 abolished minoxidil-evoked [Ca 2+ ]i rises. Overnight treatment with minoxidil killed cells at concentrations of 200–600 μM in a concentration-dependent fashion. Chelation of cytosolic Ca 2+ with 1, 2-bis(2-aminophenoxy)ethane-N, N, N', N'-tetraacetic acid/AM (BAPTA/AM) did not prevent minoxidil's cytotoxicity. Together, in PC3 cells, minoxidil induced [Ca 2+ ]i rises that involved Ca 2+ entry through PKC-regulated store-operated Ca 2+ channels and PLC-dependent Ca 2+ release from the endoplasmic reticulum. Minoxidil-induced cytotoxicity in a Ca 2+ -independent manner.